Structural and chemical characterization of corals grown under present day and naturally elevated pCO2 conditions in Papua New Guinea - a window into the future - Rothe, Nina (2015)
Dissertação de mestrado, Biologia Marinha, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015 Ocean acidification terms the process of increased CO2 uptake by surface ocean waters and a subsequent decrease in pH and carbonate ion concentration. The average pH has decreased by 0.1 since preindustrial times and is expected to drop by a further 0.3 - 0.4 until the end of the century if current anthropogenic CO2 emissions persist. This in turn will further decrease the degree of aragonite saturation in the seawater and affect the thermodynamic equilibrium of carbonate minerals (aragonite and calcite). Coral biomineralization is assumed to be strongly sensitive to the degree of saturation in the surrounding seawater, however marine carbonates are affected differently by ocean acidification and responses vary among different studies. Coral skeletons are composed of both inorganic components, usually aragonite, and organic compounds. The exact role of these organic compounds is still unknown but they are assumed to be involved in the control of carbonate precipitation. Some studies suggest, that the amount of organic compounds increases when corals grow under high CO2 and low pH conditions. In this study, the long-term effects on corals growing under high CO2 conditions at natural CO2 seeps in Papua New Guinea and under ambient CO2 conditions (control sites) were investigated as a case study and compared in terms of the amount of organic compounds in their skeletons. Three coral species were sampled and analyzed: Acropora millepora, Pocillopora damicornis and Seriatopora hystrix. Two analytical methods were investigated for their suitability to obtain information on the amount and type of organic compounds inside coral skeletons and whether any differences exist in samples collected from sites with ambient CO2 compared to increased CO2 conditions. Thermogravimetric Analysis (TGA) was used to record weight losses of powdered coral skeleton to determine the amount of hydrated organic compounds lost ...